Focused Time Saves Nine: Evaluating Computer-Assisted Protected Time for Hybrid Information Work - Swain, Vedant Das; Hernandez, Javier; Houck, Brian; Saha, Koustuv; Suh, Jina; Chaudhry, Ahad; Cho, Tenny; Guo, Wendy; Iqbal, Shamsi; Czerwinski, Mary (Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems, 2023)
Information workers often struggle to balance their time for a variety of activities like focused work, communication, and caring. This study analyzes the impact of a commercially available computer-assisted time protection intervention that automatically and preemptively schedules calendar time for self-determined activities. We analyzed the behaviors and self-reports of workers in two naturalistic studies. First, we studied 27 workers who were already using Computer-Assisted Protected Time (CAP time) and found that they mainly used it for focused work. Second, we analyzed the effect of CAP time as a randomized intervention on 89 workers who never had CAP time and found that those with it self-reported an increase in performance, job resources, and immersion. In both studies, workers with CAP time exhibited a rearrangement of activities leading to an overall reduction in work activity. This study highlights new opportunities for intelligent time-management interventions and the importance of protected time at work.